Preliminary guidelines for the rotorcraft certification by simulation process: update no. 1, March 2023 - Padfield, Gareth D.; van’t Hoff, Stefan; Lu, Linghai; Podzus, Philip; White, Mark D.; Quaranta, Giuseppe (Rotorcraft Certification by Simulation (RoCS), 2023)
This document presents preliminary Guidance for the application of (rotorcraft) flight modelling and simulation in support of certification for compliance with standards CS-27 and CS-29, PART B (Flight) and other Flight related aspects (e.g. CS-29, Appendix B, Airworthiness Criteria for Helicopter Instrument Flight). The Guidance is presented in the form of a structured process, starting from the relevant paragraphs in the Certification Specifications, through a comprehensive description of the assembly of flight simulation requirements, informed by judgements on Influence, Predictability and Credibility, and on into the detailed building of the three major elements of the process: • the flight simulation model (FSM), • the flight simulator (FS), and • the flight test measurement system (FTMS). The FTMS feeds both the flight model and simulator development with real-world test data to support validation and fidelity assessment. A structured and systematic approach to data/configuration management and documentation is recommended, aided by the creation of the Rotorcraft Certification by Simulation (RCbS) project management plan. This is the first update of the RCbS Guidelines and includes modifications based on the first round of feedback received before and after the European Rotors RoCS workshop held in Cologne on November 9th 2022. The Guidelines will continue to be updated, as appropriate, with the next major revision to include exercising the process in case studies based on applicable certification requirements from EASA CS-27 and CS-29 (to appear in Section 10). In the current update, the RoCS team have also addressed the issue of resourcing the RCbS process (within Section 9) and suggested potential next steps for aspiring applicants (new Section 11).